OPTIMALISASI DIGITAL MARKETING STRATEGY UMKM BATIK RANDU7 MULIA PROBOLINGGO - Dhany, Umi Rahma; Wilamsari, Feni; Musriati, Titik; Ngatimun, Ngatimun; Masluha, Siti (Jurnal Pengabdian Masyarakat dan Lingkungan, 2024)
The aim of this service is to provide online marketing assistance for the owners of Batik Randu 7 Mulia UMKM hand-written batik craftsmen and to provide understanding for owners and practitioners of Batik Randu 7 Mulia UMKM about the importance of online marketing in the era of globalization. The method used is described in several stages, namely identifying and solving problems, preparing a marketing plan, providing assistance in using social media and e-commerce, and evaluating activities. The most basic problem faced by partners is that marketing is still carried out conventionally. The solution offered is digital marketing management. The marketing plan carried out is making neater photos and videos, training in using marketing tools, and setting a promotional budget. Determining the right promotional media in the form of social media TikTok and Instagram. The TikTok social media that was created has a current number of followers of 60 since the last account was created. Meanwhile, Instagram social media followers have 6 followers since the last account creation.